Demographic Differences in the Factors Affecting Online Shopping Behavior in Nepal - Lamichhane, Basu Dev (NPRC Journal of Multidisciplinary Research, 2025)
Background: The e-commerce sector in Nepal is experiencing rapid growth, fueled by increasing internet penetration, smartphone adoption, and digital payment systems. Despite this momentum, its adoption remains nascent compared to global standards, hindered by challenges such as financial risks, trust issues, security concerns, and logistical inefficiencies. While existing studies have identified general psychological and technological barriers, a comprehensive understanding of how demographic factors interplay with service quality, security, and product attributes in Nepal’s unique context is lacking. Objectives: This study aims to fill this research gap by systematically investigating the multifaceted factors affecting online purchase decisions among Nepalese consumers. It specifically focuses on less-researched dimensions, including demographic influences, to provide targeted insights for enhancing consumer trust and accelerating digital commerce growth in Nepal. Materials and Methods: A quantitative, descriptive, and explanatory research design was employed. Data were collected through an online structured questionnaire from a sample of 384 Nepalese e-commerce consumers, selected using a simple random sampling technique. The survey instrument demonstrated good reliability (Cronbach’s Alpha = 0.763). Data analysis was performed using SPSS, incorporating descriptive statistics, factor analysis, and an independent samples t-test to examine gender-based differences. Findings: The findings reveal that product quality is the most critical factor (58.9% rated it extremely important), followed by price and customer service. In contrast, promotion and advertisements were perceived as the least influential. Factor analysis confirmed the strong loading of product quality (0.777) and customer ratings (0.721) on the purchase decision construct. Furthermore, a statistically significant difference was found between male and female respondents, with males attributing slightly higher importance to the combined factors overall. Conclusion: The study concludes that for Nepalese consumers, particularly the dominant youth demographic, intrinsic factors like product quality, price, and service reliability are paramount in online purchase decisions, outweighing external marketing efforts. The significant gender difference highlights the need for a nuanced understanding of the consumer base. Implication: These findings offer critical insights for e-commerce platforms, marketers, and policymakers in Nepal. To foster growth, stakeholders should prioritize ensuring product quality, transparent pricing, and robust customer service. Strategies should also be tailored to address the distinct perceptions of different demographic segments, thereby building consumer confidence and promoting the sustainable development of the e-commerce ecosystem.